Digital Transformation in Islamic Religious Education: Challenges and Opportunities for Teaching PAI in the Post-Pandemic Era - anik indramawan (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2026)
Abstract This research explores the challenges and opportunities of digital transformation in Islamic Religious Education (PAI) in the post-pandemic era. Employing a qualitative approach, the study involved interviews with PAI teachers, students, and school administrators, complemented by learning platform analysis. The results reveal that digital technology enhances learning accessibility, student engagement, and instructional creativity. However, challenges persist, including limited digital literacy, inadequate infrastructure, and pedagogical adaptation issues. The study highlights the need for capacity building and institutional support to optimize digital learning in PAI. This research contributes to understanding how Islamic education can adapt to technological change while maintaining its spiritual and ethical foundations.